2016
DOI: 10.1093/mutage/gew040
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting thein vitromicronucleus assay for evaluation of nanomaterials

Abstract: A number of in vitro methodologies have been used to assess the genotoxicity of different nanomaterials, including titanium dioxide nanoparticles (TiO NPs) and silver nanoparticles (AgNPs). The in vitro micronucleus assay is one of the most commonly used test methods for genotoxicity evaluation of nanomaterials. However, due to the novel features of nanomaterials, such as high adsorption capacity and fluorescence properties, there are unexpected interactions with experimental components and detection systems. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…No MN induction was detected when NM100 and NM101 were tested in the CBMN assay, although a slight effect was observed for NM101 in one of the tested concentrations when FC was used, supporting the advantage of the MN scoring by the last methodology (results indicated in Table 2) [19]. Moreover, negative results were also obtained when human lymphoblastoid TK6 cells were exposed to different concentrations of TiO 2 NPs [20]. Nevertheless, both studies argued that the negative results were an artifact due to Nanomaterials 2019, 9, 1677 9 of 15 the interference of the TiO 2 fluorescence with the cytometry equipment.…”
Section: Genotoxicitymentioning
confidence: 60%
See 3 more Smart Citations
“…No MN induction was detected when NM100 and NM101 were tested in the CBMN assay, although a slight effect was observed for NM101 in one of the tested concentrations when FC was used, supporting the advantage of the MN scoring by the last methodology (results indicated in Table 2) [19]. Moreover, negative results were also obtained when human lymphoblastoid TK6 cells were exposed to different concentrations of TiO 2 NPs [20]. Nevertheless, both studies argued that the negative results were an artifact due to Nanomaterials 2019, 9, 1677 9 of 15 the interference of the TiO 2 fluorescence with the cytometry equipment.…”
Section: Genotoxicitymentioning
confidence: 60%
“…Despite a large number of genotoxicity studies carried out with this nanomaterial, only a few of them used MN as a potential indicator of genotoxicity. From them, only two have recently used FC methodology to evaluate MN induction [19,20]. The evaluation of TiO 2 NPs in two different cell lines (BEAS-2B and HepG2) showed that positive effects were only observed when 10% of fetal bovine serum was used in the culture medium.…”
Section: Genotoxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…29 It is now known that the intracellular approach of apoptosis is mainly initiated by the induction of p53 as a response to DNA damage induced by genotoxic agents. 29 A number of studies have shown that nano-TiO 2 can induce DNA damage and adversely affect both major DNA repair mechanisms: base excision repair and nucleotide excision repair, showing a genotoxic potential to human cells 10,31,[42][43][44][45] and animal models. 24,46,47 We also found that the four sizes of nano-TiO 2 could induce significant DNA damages and micronuclei in human BEAS-2B cells (unpublished data).…”
Section: Discussionmentioning
confidence: 99%